The Development of Language in Elementary School-Aged Children - Herlina, Ai (International Journal of Language and Culture, 2024)
During the school years, children experience integrated development that combines various skills to handle increasingly complex tasks, including language development. Language development is an individual's ability to communicate with their environment. This communication is essential for building relationships with others, allowing individuals to feel connected to their surroundings. Language skills continue to develop throughout the school years, during which students can increasingly understand and interpret communication through speech, writing, and body language, enabling them to understand and be understood by those around them. Children develop language abilities from simple to complex forms along with their growth and development. Children learn language by imitating and repeating words used by adults, similar to how they learn other things.